Exploring factors influencing recreational participation at Templer Park , Selangor / Nawfal Kamarul Bahrain and Nurul Akmaniza Mohd Nasir - Kamarul Bahrain, Nawfal; Mohd Nasir, Nurul Akmaniza (2021)
Recreational activities are receiving much attention especially among urban communities. It is known that open green space is always capable of providing recreational opportunities to the local community. Templer Park, located between Rawang and Selayang, is seen as a strategic location to attract nearby communities from heavily populated areas to perform their recreational activities. However, the function of the park may be in doubt if the park has not successfully fulfilled the recreational needs and demands among local residents. Since more and more people are living in cities, Templer Park's function as one of the most important green spaces in the state of Selangor must be understood because people's interest for recreation activities is increasing too. Therefore, this study investigated the factors influencing participation in recreational activities at Templer Park. A total of 200 respondents were involved in this study by answering survey questionnaires regarding the factors that might contribute to their decision to choose Templer Park as a place for them to carry out recreational activities. Based on the data collected, this study found that the two main factors which put off respondents living nearby from coming to the park include being too busy with other chores and they thought that there was nothing interesting about the park that could attract them to go there. The findings showed that Templer Park is lacking in terms of being an attractive place to be visited by the residents living nearby to it; thus, there is a need of further action from the local authority to enhance the role of the park such as upgrading the signboards, updating the park information and keeping public provisions such as toilets and connecting roads in good condition in order to improve the perception of local residents toward the park.